Title: Media Participation and cultural norms around Mugambo Jwetu FM - Kimani, Rose (2019)
Community media have been lauded for the opportunity they provide to enhance participation and therefore democratic culture. In Kenya, a growing number of community radio stations have been founded partly under this logic since 2004. As of 2017, there were about 25 operational community radio stations. However, but exactly what participation consists of or what bottlenecks participation faces is not extensively laid out in either the country’s legislation or the stations’ best practices. This paper explores the daily interactions of a Kenyan ‘community radio community’ with the programmes of a radio station in their midst. It examines the media rituals at different times of the day by various sections of the community in relation to the content of the station, Mugambo Jwetu FM. Through this, the social norms that determine participation on one hand, and the new social formations that occur through participation on the other hand, are revealed. The data used are drawn from field research conducted in 2014 and 2015.